Social Work Training Intervention to Increase Referral Rates for Preventive Psychosis Services: A Randomized Trial. (March 2022) - DeVylder, Jordan E.; Andorko, Nicole D.; Smith, Melissa E.; Fitzgerald, John; Petti, Emily; Solender, Eric; Roemer, Caroline; McNamara, Karen; Buchanan, Robert W.; Schiffman, Jason
Purpose: Social workers are employed in a broad range of community settings, in which they may be able to identify youth with emerging psychotic symptoms and facilitate connection to specialized services.Methods: This randomized controlled trial tested the efficacy of a training intervention for social workers ( N = 959) intended to increase the volume of referrals and rate of successful referrals to specialized early psychosis services.Results: During the 2-year study period, referrals to the early intervention program nearly doubled, t (df = 11) = 5.46, p < 0.001. Additionally, the rate of successful referrals was greater among social workers who received the active training (41.7%) compared to the other referral sources (19.2%), X 2 (df = 1, n = 311) = 3.69, p = 0.055.Conclusions: The active training was associated with a marginally greater rate of successful referrals. Overall referrals increased greatly during the training period although this could not be linked to specific participants, suggesting contamination effects may have increased community awareness of early intervention services.